Carbon-free stacked hafnium oxide / zirconium oxide films for ferroelectric memories

By introducing Zr-doped HfO2 and nanolayer interlayered ZrO2/HfO2 alternating membrane structures into the hafnium oxide/zirconium oxide film layer, combined with ALD-type thermal deposition technology, the problem of carbon pollution in the membrane layer is solved, and a high-quality and low-carbon content film layer is achieved, which improves its electrical performance and reliability.

JP7665009B2Active Publication Date: 2025-04-18ENTEGRIS INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023502601
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-16
Filing Date
2021-07-14
Publication Date
2025-04-18
Estimated Expiration
2041-07-14

AI Technical Summary

Technical Problem

The existing hafnium oxide/zirconium oxide dielectric films are prone to carbon pollution during the preparation process, resulting in leakage and charge trap defects, affecting their electrical performance.

Method used

Using carbon-free Zr-doped HfO2 film, a high-quality film layer with a carbon content of less than 0.1 atomic percentage was prepared through nano-interlayered ZrO2 and HfO2 alternating membrane structures, combined with ALD-type thermal deposition technology.

Benefits of technology

It realizes the low carbon content of the hafnium oxide/zirconium oxide film in ferroelectric memory applications, improves its electrical performance and reliability, and is suitable for non-volatile memory based on MIM and MIS structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665009000002
    Figure 0007665009000002
  • Figure 0007665009000003
    Figure 0007665009000003
  • Figure 0007665009000001
    Figure 0007665009000001
Patent Text Reader

Abstract

Carbon-free (i.e., less than about 0.1 atomic percent carbon) Zr-doped HfO2 films are provided, where Zr can be present at levels up to the same atomic percent as Hf (i.e., 1% to 60%). Zr doping can also be achieved by nanometer-level stacked ZrO2 and HfO2 films useful for ferroelectric random access memories (FeRAMs). The stacked films are composed of about 5 to 10 layers of HfO2 and ZrO2 (i.e., alternating) films, each of which can be, for example, about 1 to about 2 nm thick, for a total stacked film thickness of about 5 to 10 nm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention is in the field of microelectronics, and more particularly, the present invention relates to improved ferroelectric memory materials and structures comprising hafnium dioxide films, zirconium dioxide films, mixed compositions of hafnium dioxide and zirconium dioxide, and electrodes. [Background technology]

[0002] Certain electronic devices have the ability to store and retrieve information in memory structures or cells. Such memory cells are configured to store information in bits. For example, a memory cell may have at least two states representing a logical one and a logical zero. Information thus stored may be read by determining the state of the memory cell. Such cells may be integrated on a wafer or chip with one or more logic circuits.

[0003] One type of volatile memory is the DRAM structure, which allows high speed and large capacity data storage. Examples of non-volatile memory structures include ROM, flash structures, ferroelectric structures (e.g., FeRAM and FeFET devices), and MRAM structures.

[0004] In the case of ferroelectric structures, they can be adapted in the form of capacitors (e.g., FeRAM) or transistors (FeFET), and information can be stored as a particular polarization state of the ferroelectric material within the structure. One example of a ferroelectric material and structure utilizes a transition metal oxide, such as hafnium dioxide mixed with zirconium dioxide.

[0005] Dielectric films composed of hafnium oxide and zirconium oxide are typically prepared using atomic layer deposition and / or chemical vapor deposition techniques using organometallic hafnium and zirconium dialkylamide precursors. See, for example, "Atomic Layer Deposition of Hafnium and Zirconium Oxides using Metal Amide Precursors," Dennis M. Hausmann et al., Chem. Mater. 2002, 14, 4350-4358. Unfortunately, such methodologies result in dielectric films that have low levels of carbon contamination that result in leakage and charge trapping defects in the hafnium oxide / zirconium oxide dielectric films. These films can also generate carbon during subsequent process steps during device fabrication, thereby altering the properties of the film. Thus, there is a need for methodologies to produce such dielectric films that do not have these levels of carbon and therefore their attendant disadvantages. Summary of the Invention

[0006] In summary, the present invention provides carbon-free (i.e., less than about 0.1 atomic percent carbon) Zr-doped HfO2 films, where Zr can be up to the same level as Hf in atomic percent (i.e., about 1% to about 60%, or about 45% to about 55% or about 50% via co-introduction of precursors). Zr doping can also be effectively achieved by nanometer stacked ZrO2 and HfO2 films (1% to 60% Zr compared to Hf) useful for ferroelectric memories (FeRAM). The stacked films are composed of about 5 to 10 layers of HfO2 and ZrO2 (i.e., alternating) films, each of which can be, for example, about 1 to about 2 nm thick, with the stacked films being about 5 to 20 nm thick in total. The stacked films of the present invention are expected to exhibit excellent ferroelectric and electrical properties for use in MIM (metal-insulator-metal) and MIS (metal-insulator-silicon (or other channel)) structure based ferroelectric memory applications. Such non-volatile memories generally achieve high density, low power, fast switching, low cost, and high endurance.

[0007] The stacked films of the present invention can be prepared using an ALD-type thermal deposition technique utilizing HfCl4 (or HfBr4 or HfI4) and ZrCl4 (or ZrBr4 or ZrI4) and an oxidizing gas such as ozone, oxygen, water, N2O, or plasma O2 as a co-reactant to deposit high quality carbon-free films of HfO2 and ZrO2, respectively.

[0008] The present invention also provides methodologies for using HfCl4, HfBr4, HfI4, ZrCl4, ZrBr4, and ZrI4 to deposit hafnium oxide and zirconium oxide films having less than about 0.1 atomic percent carbon. Additionally, such films may also contain less than about 0.1 atomic percent of the corresponding halogen, such as chlorine, bromine, or iodine.

[0009] In a metal-insulator-metal (MIM) memory device embodiment, the laminated hafnium oxide / zirconium oxide film of the present invention has top and bottom layers composed of at least one of titanium nitride, ruthenium, molybdenum, iridium, cobalt, tungsten, platinum, or conductive oxides of iridium and ruthenium as electrodes. The top and bottom layers as electrodes may or may not be the same material. In a metal-insulator-semiconductor (MIS) memory device embodiment, the laminated hafnium oxide / zirconium oxide film may be directly deposited on the semiconductor and top layers as electrodes composed of at least one of titanium nitride, ruthenium, molybdenum, iridium, cobalt, tungsten, platinum, or conductive oxides of iridium and ruthenium.

[0010] In a further embodiment, the layered hafnium oxide / zirconium oxide film of the present invention further comprises at least one outer surface comprised of iridium or iridium oxide, hi a further embodiment, the layered hafnium oxide / zirconium oxide film of the present invention further comprises at least one outer surface comprised of titanium nitride. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a cross-sectional view of a laminated structure of the present invention adapted to form a MIM structure for memory applications (FeRAM). [Diagram 2] FIG. 1 is a cross-sectional view of a laminate structure of the present invention adapted to form a MIS structure for FeFET applications. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] In the film stack of the present invention, the initial or "starting" film can be either hafnium oxide or zirconium oxide, and similarly the final or "finishing" film can be either hafnium oxide or zirconium oxide, as depicted in Figures 1 and 2. In Figures 1 and 2, hafnium oxide is depicted as the starting film and zirconium oxide is depicted as the finishing film.

[0013] In Figures 1 and 2, the dark black layers indicate metal layers, the white layers indicate layers of hafnium oxide, the grey layers (Figure 1) represent zirconium oxide layers, and the light grey layers (Figure 2) indicate layers containing silicon or other channel materials.

[0014] In one aspect, the invention provides a hafnium oxide film, the hafnium oxide film is doped with about 1 to about 60 atomic percent zirconium oxide, based on the total atomic percent of the film, the film containing less than about 0.1 atomic percent carbon and less than about 0.1 atomic percent halogens. In other embodiments, the film is doped with about 45 to 55, or about 50 atomic percent zirconium oxide.

[0015] In a second aspect, the present invention provides a laminate film comprising alternating layers of hafnium oxide and zirconium oxide, the laminate film having a thickness of about 5 to about 10 nm, the laminate film having less than about 0.1 atomic percent carbon.

[0016] In one embodiment, the top and bottom films are hafnium oxide. In another embodiment, the top and bottom films are zirconium oxide. In another embodiment, the film stack further comprises at least one dopant element selected from silicon, aluminum, yttrium, and lanthanum.

[0017] 1, the laminated film (i.e., ferroelectric stack) may further comprise a metal layer on each side, in certain embodiments, the metal layer is composed of titanium nitride, ruthenium, molybdenum, iridium, cobalt, tungsten, platinum, or a conductive oxide of iridium or ruthenium.

[0018] As discussed above in FIG. 2, the film stack may further comprise a metal layer or surface on one side and a silicon film or silicon-containing film on the other side (e.g., Si 1-x Ge x where x is greater than 0 but less than 1 and represents the various percentages of each element in the alloy, referred to herein as "SiGe" for simplicity.

[0019] In a further embodiment, the layered hafnium oxide / zirconium oxide film of the present invention further comprises at least one outer surface comprised of iridium or iridium oxide.

[0020] In a further embodiment, the layered hafnium oxide / zirconium oxide film of the present invention further comprises at least one outer surface comprised of at least one of titanium nitride, ruthenium, molybdenum, iridium, cobalt, tungsten, platinum, or conductive oxides of iridium and ruthenium, hi one embodiment, at least one outer surface is titanium nitride.

[0021] In one embodiment, the layered hafnium oxide / zirconium oxide film of the present invention has a top layer (i.e., film) composed of at least one of iridium and iridium oxide, and / or a bottom layer (i.e., film) of at least one of titanium nitride, iridium, or iridium oxide, either of which are used as electrodes in a memory stack assembly.

[0022] Hafnium oxide and zirconium oxide films having less than about 0.1 atomic percent carbon can be deposited as films on substrates, such as microelectronic device substrates, by utilizing a vapor deposition (ie, thermal) process.

[0023] In certain embodiments, deposition conditions include reaction conditions known as chemical vapor deposition, pulsed chemical vapor deposition, and atomic layer deposition. In the case of pulsed chemical vapor deposition, a series of alternating pulses of precursor compounds and co-reactants, with or without intermediate (inert gas) purge steps, can be utilized to build film thickness to a desired endpoint.

[0024] In certain embodiments, the pulse time of the precursor compounds (i.e., duration of precursor exposure to the substrate) ranges from about 0.1 to 10 seconds. If a purge step is utilized, the duration is about 1 to 4 seconds or 1 to 2 seconds. In other embodiments, the pulse time of the co-reactant ranges from 1 to 60 seconds. In other embodiments, the pulse time of the co-reactant ranges from about 1 to about 10 seconds.

[0025] In one embodiment, the deposition conditions include a temperature of about 250° C. to about 750° C. and a pressure of about 1 to about 1000 Torr. In another embodiment, the deposition conditions include a temperature of about 250° C. to about 650° C.

[0026] Hafnium tetrachloride (or hafnium iodide) and zirconium tetrachloride (or zirconium iodide) may be employed to form high purity hafnium dioxide and zirconium dioxide containing films by any suitable deposition technique, such as CVD, digital (pulsed) CVD, ALD, and pulsed plasma processes. Such deposition processes may be utilized to form such films on microelectronic devices by utilizing deposition temperatures of about 250° to about 550° C. to form films having thicknesses of about 20 Angstroms to about 2000 Angstroms.

[0027] In the processes of the present invention, the compounds may be reacted with the desired microelectronic device substrate in any suitable manner, such as in a single wafer CVD, ALD, and / or PECVD or PEALD chamber, or in a furnace containing multiple wafers.

[0028] Alternatively, the process of the present invention can be carried out as an ALD or ALD-like process. As used herein, the term "ALD or ALD-like" refers to a process in which (i) reactants including hafnium or zirconium precursor compound (I) and oxidizing gas are introduced sequentially into a reactor, such as a single-wafer ALD reactor, a semi-batch ALD reactor, or a batch furnace ALD reactor, or (ii) reactants including precursor compound and oxidizing gas are exposed to the substrate or microelectronic device surface by moving or rotating the substrate to different compartments of the reactor, each compartment being separated by an inert gas curtain, i.e., a spatial ALD reactor or a roll-to-roll ALD reactor.

[0029] As noted above, the deposition process may further include a step involving exposing the substrate to an oxidizing gas, such as O2, O3, N2O, water vapor, alcohol, or oxygen plasma. In certain embodiments, the oxidizing gas further includes an inert carrier gas, such as argon, helium, nitrogen, or combinations thereof.

[0030] The deposition methods disclosed herein may involve one or more purge gases. Purge gases used to purge away unconsumed reactants and / or reaction by-products are inert gases that do not react with the precursors. Exemplary purge gases include, but are not limited to, argon, nitrogen, helium, neon, hydrogen, and mixtures thereof. In certain embodiments, a purge gas, such as nitrogen or argon, is fed into the reactor at a flow rate ranging from about 10 to about 2000 sccm for about 0.1 to 1000 seconds, thereby purging unreacted materials and any by-products that may remain in the reactor.

[0031] Energy is applied to at least one of the precursor compound and the oxidizing gas to induce a reaction and form a hafnium dioxide or zirconium dioxide film on the microelectronic device substrate. Such energy may be provided by, but is not limited to, thermal, pulsed thermal, plasma, pulsed plasma, helicon plasma, high density plasma, inductively coupled plasma, x-ray, electron beam, photon, remote plasma methods, and combinations thereof. In certain embodiments, a secondary RF frequency source may be used to modify the plasma characteristics at the substrate surface. In embodiments where deposition involves plasma, the plasma generation process may include a direct plasma generation process where the plasma is generated directly in the reactor, or alternatively, a remote plasma generation process where the plasma is generated "remote" to the reaction zone and substrate and fed into the reactor.

[0032] In one embodiment, the film is deposited using atomic layer deposition techniques, for example, utilizing an ASM Pulsar® XP ALD reactor. By way of example, the deposition process can be carried out under the following conditions: HfCl4 (or ZrCl4) ampoule temperature = 170℃ H2O ampoule temperature: 18~20℃ Pressure = 2~3 Torr Flow rate = 400-600sccm (100-200 through HfCl4 (or ZrCl4)) ampule The substrate (i.e., chamber) temperature (T 基板 )=300℃ HfCl4 (or ZrCl4) pulse = 0.5 to 1 second H20 pulse = 0.1 to 0.2 seconds

[0033] In another example of atomic layer deposition, HfCl4 (or ZrCl4) can be deposited on a 300 mm bare silicon wafer under the following conditions: TIFF0007665009000001.tif34170

[0034] As noted above, in other embodiments, films so formed utilizing this methodology also have less than about 0.1 atomic percent of halogens, such as iodine, bromide, and chlorine.

[0035] Thus, in a further aspect, the present invention provides a method for depositing a hafnium oxide film on a substrate using HfCl4, HfBr4, or HfI4, the film having less than about 0.1 atomic percent carbon, the method comprising alternatingly exposing the substrate to (i) HfCl4, HfBr4, or HfI4, and (ii) an oxidizing gas under deposition conditions in a reaction zone. In one embodiment, the film has less than about 0.1 atomic percent halogen.

[0036] In a further aspect, the present invention provides a method for depositing a zirconium oxide film on a substrate using ZrCl4, ZrBr4, or ZrI4, the film having less than about 0.1 atomic percent carbon, the method comprising alternatingly exposing the substrate to (i) ZrCl4, ZrBr4, or ZrI4, and (ii) an oxidizing gas under deposition conditions in a reaction zone. In another embodiment, the film has less than about 0.1 atomic percent halogen.

[0037] Insofar as hafnium tetrachloride (and hafnium tetraiodide) and zirconium tetrachloride (and zirconium iodide) are solids at room temperature, a storage and delivery device such as the ProE-Vap® 100 delivery system sold by Entegris, Inc. may be advantageously utilized. See also U.S. Pat. Nos. 10,465,286, 10,392,700, 10,385,452, 9,469,89, and 9,004,462, which are incorporated herein by reference. Thus, configurations with dual solid delivery systems such as these may be utilized in a vapor deposition process for preparing laminated films as described above by alternately depositing hafnium dioxide and zirconium dioxide.

[0038] The invention has been described in detail with particular reference to certain embodiments thereof, but it will be understood that variations and modifications can be effected within the spirit and scope of the invention.

Claims

1. 1. A laminate film comprising a mixed film of alternating layers of hafnium oxide and zirconium oxide layers, the laminate film having a thickness of 5-10 nm, the laminate film having less than 0.1 atomic percent carbon, the atomic percentage of zirconium relative to the sum of hafnium and zirconium atoms in the laminate film being in the range of 45%-55%, the laminate film having a top layer comprised of at least one of iridium and iridium oxide, and a bottom layer of titanium nitride.

2. The laminate film described in claim 1, further comprising at least one dopant selected from silicon, aluminum, yttrium, and lanthanum.

3. 10. The film of claim 1, containing less than 0.1 atomic percent halogen.

4. A method for forming a laminated film including a mixed film of a plurality of alternating layers of hafnium oxide and zirconium oxide layers, comprising the steps of: (i) depositing a mixture of HfCl 4 , HfBr 2 and HfCl 4 under deposition conditions in a reaction zone; 4 , or HfI 4 and (ii) alternately introducing an oxidizing gas into the hafnium oxide layer to deposit the hafnium oxide layer; 13. A method for manufacturing a semiconductor device comprising: a film stack having a thickness of 5-10 nm; the film stack having less than 0.1 atomic percent carbon; an atomic percentage of zirconium relative to the sum of hafnium and zirconium atoms in the film stack ranging from 45% to 55%; and the film stack having a top layer composed of at least one of iridium and iridium oxide and a bottom layer of titanium nitride.

5. A method for forming a laminated film including a mixed film of a plurality of alternating layers of hafnium oxide and zirconium oxide layers, the method comprising the steps of: (i) depositing, under deposition conditions in a reaction zone, ZrCl4, ZrBr 4 or ZrI4, and (ii) an oxidizing gas to deposit said zirconium oxide layer; 13. A method for manufacturing a semiconductor device comprising: a film stack having a thickness of 5-10 nm; the film stack having less than 0.1 atomic percent carbon; an atomic percentage of zirconium relative to the sum of hafnium and zirconium atoms in the film stack ranging from 45% to 55%; and the film stack having a top layer composed of at least one of iridium and iridium oxide and a bottom layer of titanium nitride.

Citation Information

Patent Citations

  • Metallic amide precursor and amino silane precursor for CVD forming dielectric thin film

    JP2008300850A

  • Atomic layer deposition of metal oxide materials for memory applications

    JP2014531749A

  • Atomic layer deposited nanolaminates of HfO2 / ZrO2 films as gate dielectrics

    US20040023461A1

  • Methods to form dielectric structures in semiconductor devices and resulting devices

    US20080087890A1

  • Semiconductor device having high-k gate dielectric layer and manufacturing method thereof

    US20130043545A1